Radial Distributions of Active Species in RF-Jet Plasmas and Afterglows - André Ricard; Joelle Margot; Soo-Ghee Oh (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
The radial distributions of plasma and afterglow radiative species have been analyzed with optical fibers connected to an optical spectrometer. With an optical fiber of 1 mm dia. giving a detected light resolution of about 1 cm at a 10 cm distance, the N2 long time afterglow (LA-10-2 s) was studied in a large volume reactor (5 liters). At a pressure of 68 Torr, flow rate 0.5 - 1 slpm, the LA at 10-2 s was a jet of dia. 2 cm with densities of N-atoms and N2(X, v > 13) metastable molecules of 1015 and 0.5 1015 cm-3, respectively. By putting a horizontal slit of 50\(mu\)m in front of the dia. 1 mm optical fiber, a light beam of 1 mm dia. was detected across an afterglow tube of 2 cm dia. In an N2 RF plasma at 8 Torr, 1slpm, 100 W, Bessel-typed profiles were recorded for all the radiative bands in the pink afterglow and flat profiles of the N2 580 nm band in the late afterglow. The N2 580 nm band is produced in the late afterglow by N-atoms rebounding on the tube wall, explaining its flat profile. In the pink afterglow, the N2580 nm band is mainly produced by collisions of the N2(X, v > 13) and N2(A) states where N2(A) is destroyed on the tube wall, which explains its Bessel profile. With a small H2 content into N2, the N2(X, v > 13) and N2(A) states in the pink afterglow are destroyed, lowering the N2 580 nm emission that was only produced by the N atoms, yielding a flat profile. A 1 mm radial profile was also obtained with a collimator set on the 1 mm optical fiber and moved along the radial axis of a surface wave (SW) plasma. With a SW plasma, the electric field (E) reaches a maximum value on the tube wall giving high energy to electrons. As a consequence, the Ar metastable atoms produced by high energy electrons and destroyed by low energy electrons (insensitive to E) will show radial profiles of which the shapes were analyzed to determine the metastable excitation (CM) and de-excitation (CM) rates. In Ar SW plasmas at 600MHz, 0.1 Torr, 2 W, it was determined that CM = (1 - 5)10-11 cm3 s-1 and CM = (1 - 3)10-7 cm3 s-1 as for a DC positive column at same electron density: ne = 31010 cm-3. 3D spatial distributions of the intensity of the optical thin ArI 549.6 nm line were measured in DC and SW plasma columns at 150 mTorr inside tubes of 2 cm dia. and 50 cm long. Bessel-type radial distributions were found in the Ar DC column and more rounded profiles in the Ar SW plasmas at 600 - 900 MHz, with hollow shapes at the plasma end.